PERSEPSI MASYARAKAT TERKAIT PENERAPAN KONSEP DESAIN EKOLOGI TERHADAP PEMBANGUNAN BERKELANJUTAN PADA TEPIAN SUNGAI AYUNG - PRAGANINGRUM, TJOKORDA ISTRI; WANGSA, ANAK AGUNG RATU RITAKA; GRAHA, I MADE SATYA; PRADNYADARI, NI LUH MADE AYU MIRAYANI (Universitas Mahasaraswati K. Mataram, 2023)
The concept of sustainable development has basically become the concern of all parties, especially in tourist destination areas. The Ayung riverside area is one of the tourist destinations for local and foreign residents. The rapid development of the Ayung riverside environment has a great impact on the environment around the village. The environment around the village sometimes becomes a place of uncontrolled development that causes environmental damage characterized by decreased air, water and soil quality, resulting in the extinction of animals, plants, wildlife and damage to ecosystems. In this context, it is necessary to apply ecological architecture to the construction of urban support works, including riverside areas. This study aims to determine public perceptions related to the application of ecological design concepts to sustainable development in the Ayung riverside area. The method used is descriptive with a qualitative approach, analyzing according to the principles of ecological design. The application of ecological architecture on the banks of the Ayung river is expected to ensure the sustainability of the ecosystem and minimize negative impacts on the environment due to improper ecological design. The results of this study show that ecological principles can be applied in the Ayung riverside area, including the arrangement of several buildings to create dynamic green spaces while still based on local wisdom